Identification of Anthocyanidins in Anthocyanin Extract of Purple Sweet Potato (Ipomoea batatas l), black rice (Oryza sativa l), and Black Glutinous rice (Oryza sativa v. glutinosa) - Sumartini, Sumartini (Journal Akademik Universitas Swiss German, 2023)
Anthocyanins originating from different commodities have different constituent components and anthocyanidin levels. This will undoubtedly affect the anthocyanin content of total in foodstuffs. Local items such as; Purple sweet potato, black rice, and black glutinous rice have different structural components and levels of anthocyanidins. The research objective was to measure the total anthocyanin content and identify anthocyanidins qualitatively and quantitatively from anthocyanin extracts of purple sweet potato, black rice, and black glutinous rice. The research method used was an experimental method , qualitative and quantitative identification analyses were carried out using the UHPLC-PDA (Ultra high Performance Liquid Chromatographic) instrument system. Based on the study with pH-difference measurements, the total anthocyanin extract in purple sweet potato is 0.6 mg / g of material, much lower than black rice (5.50 mg / g of material) and black glutinous rice (6.00 mg / g of material). g material). Based on the identification of the purple sweet potato anthocyanin extract, the main components of anthocyanidins were Delfinidin, Cyanidin, and Malvidin with concentrations of 0.12 mg, 0.12 mg, and 1.20mg / 100g of ingredients, respectively. Meanwhile, black rice and black glutinous rice were identified with cyanidine and malvidin with concentrations of 0.73 and 13.17 mg / 100g and 1.07 mg and 17.6 mg / 100g of ingredients.